SOSIALISASI APLIKASI MERDEKA MENGAJAR DAN PENGENALAN PLATFORM SIMBA DALAM MENINGKATKAN PEMAHAMAN MEDIA PEMBELAJARAN KEPADA TENAGA PENDIDIK DI SMPN 10 CILEGON - Dewi Surani; Aas Nur Asnawati; Asensa Widia Kusuma (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
The Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) has made the Merdeka Mengajar application on Merdeka Belajar Episode 15. This stage is an application that can uphold educators in carrying out the Independent Education program. In accordance with the Minister of Education and Culture, Nadiem Makarim, in making the Merdeka Education curriculum and the Merdeka Teaching application on February 11, 2022, the Merdeka Mengajar application is an application for educators that will be formed into an application that is not only material content and services, but is actually owned by teachers, from teachers, for teachers. So, here's an app to implement a free education plan and look for ways to improve as an instructor,". Furthermore, the Minister of Education and Culture revealed that the Merdeka Mengajar stage will be a companion for educators in teaching and this stage will also help educators to improve in picking up in accordance with the times. The creation of this independent teaching application is not only to help the implementation of independent education programs in driving schools, but can also be used by all teachers and train staff in educational units that are not yet driving schools, because the independent curriculum is the school's decision in implementing education plans in training units. So in general, the Merdeka Mengajar application is one of the stages of innovation given to help instructors to perform better, hone their skills, and foster a profession. Starting from our intention to reduce the burden on educators in students in the digital learning process, the idea emerged to create an Android application whose user interface is similar to the final exam of students which is a computer-based national exam (UNBK). From the results of our thinking, a learning simulation (SIMBA) was made. With the aim of introducing students to UNBK KKM participants of Bina Bangsa University. Conducting research on related schools at the location of student work lectures (KKM) in the Suralaya Village area, with a high level of learning motivation makes us even more motivated to develop this platform